2005
DOI: 10.1016/j.jog.2004.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Upper mantle viscosity from continuous GPS baselines in Fennoscandia

Abstract: The permanently recording BIFROST (Baseline Inferences for Fennoscandian Rebound Observations, Sea Level and Tectonics) GPS network was set into operation during the early to mid-1990s to monitor the three-dimensional crustal deformation field in Fennoscandia. We have employed 2500 days of BIFROST GPS data to estimate rates of baseline component change (length, transverse and up). Baselines are less sensitive than single-site position estimates to perturbations in satellite orbits and reference frame realizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Moreover, xenolith and other evidence indicate that subduction introduces copious amounts of water, whereas mantle at the base of stable continental lithosphere (>150 km depth) is comparatively dry [e.g., Dixon et al , 2004]. Modeling of Pleistocene lake rebound [ Bills , 1994; Bills et al , 2007] and recent alpine deglaciation [ Larsen et al , 2004] indicates viscosity of ∼10 18 –10 19 Pa s in regions of recent or active subduction, whereas asthenospheric viscosity of 10 20 –10 21 Pa s is required for postglacial rebound under stable continental lithosphere [ Bergstrand et al , 2005; Peltier and Jiang , 1996]. If asthenosphere from beneath thick continental lithosphere is entrained into wedge flow, and diffusion of slab‐derived water is not sufficiently rapid to immediately hydrate the wedge, viscosities ≥10 20 Pa s required for flat subduction may be attained.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, xenolith and other evidence indicate that subduction introduces copious amounts of water, whereas mantle at the base of stable continental lithosphere (>150 km depth) is comparatively dry [e.g., Dixon et al , 2004]. Modeling of Pleistocene lake rebound [ Bills , 1994; Bills et al , 2007] and recent alpine deglaciation [ Larsen et al , 2004] indicates viscosity of ∼10 18 –10 19 Pa s in regions of recent or active subduction, whereas asthenospheric viscosity of 10 20 –10 21 Pa s is required for postglacial rebound under stable continental lithosphere [ Bergstrand et al , 2005; Peltier and Jiang , 1996]. If asthenosphere from beneath thick continental lithosphere is entrained into wedge flow, and diffusion of slab‐derived water is not sufficiently rapid to immediately hydrate the wedge, viscosities ≥10 20 Pa s required for flat subduction may be attained.…”
Section: Discussionmentioning
confidence: 99%
“…Scherneck et al, 1998Scherneck et al, , 2003Milne et al, 2001;Johansson et al, 2002;Lidberg et al, 2007Lidberg et al, , 2010 and also used in GIA modeling (e.g. Milne et al, 2001Milne et al, , 2004Bergstrand et al, 2005;Steffen and Kaufmann, 2005;Steffen et al, 2006Steffen et al, , 2007Lidberg et al, 2007Lidberg et al, , 2010Wu et al, 2010). Scherneck et al (2010) obtained first results of strain rate determination from BIFROST velocities.…”
Section: Gpsmentioning
confidence: 99%
“…Based on BIFROST GPS data, Milne et al (2001) and Milne et al (2004) derived a radial viscosity profile with permitted lithospheric thickness values between 90 and 170 km, upper-mantle viscosities in the range of (5-10) ×10 20 Pa s, and lower-mantle viscosities in the range of (0.5-5) ×10 22 Pa s. The latest derived BIFROST GPS velocity field presented in Lidberg et al (2007) was used by Lidberg et al (2010) and led to an optimal model that is defined by a 120-km thick lithosphere, an upper-mantle viscosity of 5 × 10 20 Pa s and a lower-mantle viscosity of 5 × 10 21 Pa s. Bergstrand et al (2005) also employed BIFROST data and found that a lithospheric thickness of 120 km and an upper-mantle viscosity in the range (3-10) ×10 20 Pa s is preferred. Davis et al (1999) presented modeling results from tide-gauge data.…”
Section: Radial Profilementioning
confidence: 99%
“…First, it strongly varies laterally while we only assume a 1D Earth model. Second, there is a trade-off between the assumed lithospheric thickness and the obtained mantle viscosity values (Bergstrand et al, 2005). Hence, an erroneous assumption of lithospheric thickness can lead to errors in the mantle viscosity estimations.…”
Section: Other Influencesmentioning
confidence: 99%